KONSEPTUAL MOTIVASI KERJA DI LEMBAGA PENDIDIKAN ISLAM - nursyamsiyah, siti (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2020)
The concept of motivation Maslow's ideas "" self-actualization is the person's motivation to transform perception of self into reality ". Motivation is the most basic factor in educational institutions to mobilize human resources potential to grow enthusiasm in working with organizational objectives. The second factor is the leader as a leader able to mobilize human resources. Sensitivity of a leader is expected to understand the nature and human needs. Hierarchy of human needs is expected to be another consideration in motivating staff, teachers (cleric) or employees. Five things humans need to note are: physiological, safety, social, esteem and self-actualization needs. If a leader promoting the values of humanity in motivating subordinates